Stepped waveform generation for multilevel inverter topology applications - Tohtayong, Majdee; Khan, Sheroz; Yusoff, Siti Hajar; Yaacob, Mashkuri; Ahmed, Musse Mohamud; Motakabber, S. M. A.; Aboadla, Ezzidin Hassan Elmabrouk (IEEE, 2016)
This paper presents a review of the various inverter topologies, showing their utility in generating stepped waveform. The role of the PWM is highlighted in the operation of inverter for generating stepped-wave forms. The results show how similarly generated PWM used by different topologies can result into a stepped-waveform output capable of producing and AC closer to single fundamental component of 50Hz. The total harmonic Distortion (THD) is given for each set of simulation result with a relatively marked, though marginal utility, of the PWM used